Innovation ecosystems and sustainable technologies : enhancing competitiveness and sustainability - Singh, Rubee; Corvello, Vincenzo; Coniglio, Iida Maria; Khan, Shahbaz (Emerald Publishing Limited, 2025)
Innovation Ecosystems and Sustainable Technologies: Enhancing Competitiveness and Sustainability draws connections between innovation ecosystems and sustainable development to seek ways of improving economic, environmental and social wellbeing based on improvements to the innovation ecosystems. The book sheds light on various advancements in innovation ecosystems and emerging technologies for the purpose of sustainability and aims to address the urgency of responding to the UN Sustainable Development Goals (UN-SDGs). The book presents a unique perspective in terms of its exploration and integration of innovative multi-disciplinary ideas, techniques, and tools that are critical for the implementation of innovative ideas, technologies, and tools for sustainability. Innovation Ecosystems and Sustainable Technologies is a great resource to learn how emerging technologies such as artificial intelligence, Internet of Things, and cloud technologies are transforming innovation ecosystems and promoting sustainability. The focus on transitioning to an Innovation Ecosystem, sustainability, and emerging technologies in an increasingly globalised world, makes it perfect for policymakers, researchers, and company leaders alike. The series Emerald Studies in Sustainable Innovation Management aims at exploring the advancements of innovation management in turbulent times with a special attention to the transition towards a sustainable economy. The practice of innovation management is evolving rapidly as a consequence of positive phenomena such as digitalization and the green transition and negative ones such as crises and global emergencies.
Keywords: Sustainability -- Technological innovations.; Biotic communities.; Technological innovations.; Business & Economics -- Environmental Economics.; Business and the environment; green approaches to business.; Environmental economics.; elektronické knihy; electronic books